STRATEGI DAN PELUANG PENGAJARAN AGAMA ISLAM DALAM PEMBELAJARAN BERBASIS MULTIKULTURAL - -, Asih Kartika Putri (Rabbani: Jurnal Pendidikan Agama Islam, 2022)
Religious education as a form of culture must of course be in line with religious education in a society. In the world of education, there is diversity and diversity of students. Often because of this diversity, frictions arise that cause social conflicts, especially in the world of education. To minimize friction, teaching through a cross-cultural approach is needed. Multicultural education is a model of providing education that carries an ideology that understands, respects, and respects human dignity from anywhere and from anywhere (economic, social, cultural, ethnic), language or religion, and depends on the country. In this case, a learning strategy that adopts a cross-cultural approach is needed in teaching religion is needed. Teaching Islam through a cross-cultural approach can be done with a strategy of self-organization, management and administration of Islamic religious education. This study examines how Islamic learning is achieved using a multicultural approach, where the element that evokes a sense of tolerance for ethnicity, culture, ethnicity and other diversity is significant, that every human being has great tolerance. The purpose of this research is to describe, study, analyze and apply in everyday life to make life better and respect differences and mutual tolerance.